The present and future disease burden of hepatitis C virus infections with today's treatment paradigm: Volume 4. (4th November 2017) - Chan, H. L. Y.; Chen, C. J.; Omede, O.; Al Qamish, J.; Al Naamani, K.; Bane, A.; Tan, S. S.; Simonova, M.; Cardenas, I.; Derbala, M.; Akin, O.; Phillips, R. O.; et al.
Summary: Factors influencing the morbidity and mortality associated with viremic hepatitis C virus (HCV) infection change over time and place, making it difficult to compare reported estimates. Models were developed for 17 countries (Bahrain, Bulgaria, Cameroon, Colombia, Croatia, Dominican Republic, Ethiopia, Ghana, Hong Kong, Jordan, Kazakhstan, Malaysia, Morocco, Nigeria, Qatar and Taiwan) to quantify and characterize the viremic population as well as forecast the changes in the infected population and the corresponding disease burden from 2015 to 2030. Model inputs were agreed upon through expert consensus, and a standardized methodology was followed to allow for comparison across countries. The viremic prevalence is expected to remain constant or decline in all but four countries (Ethiopia, Ghana, Jordan and Oman); however, HCV‐related morbidity and mortality will increase in all countries except Qatar and Taiwan. In Qatar, the high‐treatment rate will contribute to a reduction in total cases and HCV‐related morbidity by 2030. In the remaining countries, however, the current treatment paradigm will be insufficient to achieve large reductions in HCV‐related morbidity and mortality.